A Review of Change Detection in Multitemporal Hyperspectral Images: Current Techniques, Applications, and Challenges - Liu, Sicong; Marinelli, Daniele; Bruzzone, Lorenzo; Bovolo, Francesca (IEEE geoscience and remote sensing magazine, 2019)
We review both widely used methods and new techniques proposed in the recent literature. The basic concepts, categories, open issues, and challenges related to CD in HS images are discussed and analyzed in detail. Experimental results obtained using state-of-the-art approaches are shown, to illustrate relevant concepts and problems.